(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s
(3ChdgG (B:s
(3gPg GdebGdI JJVef UaGJ GdeSgdGJ hbO bSeJ gPg GdebGdI Ydi SHYI CHhGH s
(3BNQgG (B:s
(3hVYa GdHUQ hfRhd GdeGA , jDNP HYUjQ GdQGQfGfL MJi jNJdW hjUjQ eKd GdYSd , hGcJMd Hg , fGaY Ef TGA Gddg s
(3fSNI QGHYIs
(3JHOG HGdebGdI GdQGHYI YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs